2021
DOI: 10.29235/1561-8323-2021-65-2-207-216
|View full text |Cite
|
Sign up to set email alerts
|

The influence of old age on cardioprotective efficiency of pharmacological postconditioning using lactic acid in ischemia-reperfusion of the myocardium in experiment

Abstract: Not only the prevalence, but also the death rate from the coronary heart disease, including myocardial infarction, is higher in older people than among young people. A demographic shift towards an aging population will lead to a further increase in the prevalence of cardiovascular diseases among the elderly population. Therefore, one of the urgent aims of modern experimental and clinical medicine is to develop methods aimed at limiting reversible and irreversible damage to the myocardium, including in elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recently, it has been demonstrated that exogenous lactate can mimic RPost in rats [ 35 ]. It is possible that lactate released from skeletal muscle can trigger RPost in limb I/R.…”
Section: Experimental Datamentioning
confidence: 99%
“…Recently, it has been demonstrated that exogenous lactate can mimic RPost in rats [ 35 ]. It is possible that lactate released from skeletal muscle can trigger RPost in limb I/R.…”
Section: Experimental Datamentioning
confidence: 99%